Una herramienta para la integración a la educación regular de estudiantes que presentan necesidades educativas especiales (Educational Perspectives Magazine (REPED), 2023)
The present article is removed of an investigation performed around the curriculum adaptations that are carry out to facilítate the school integration of those students that present special educational needs (NEE) associates to disability, and that at present they form part of public educational establishments and individuáis subsidized of the common of Ñuñoa and Peñalolén.The fundamental objective of this study, search as central axis to arrive at the comprehension of the to drive educational of those educational that particípate in a Project of School Integration (PIE), and that therefore, they should devise curriculum adaptations that they lead to a real integration of students with disability to the system of regular education, facilitating their process of learning in function of their achievements and potentialities.Finally, the analysis of the results obtained, revealed that the main obstacles that exhibits the process of school integration, they are above-mentioned to the lack of training of the educational to carry out curriculum adaptations, to the ignorance of methodologies and innovative strategies focused to the specific needs of each student, and to the shortage of necessary resources that facilítate their pedagogical work in the classroom. In this way, the present article has as purpose to bring to light the most prominent finds, arisen since the information delivered by the educational that participated in this study.
Keywords: Curriculum adaptations, Special Educational Needs (NEE), School Integration.